The 'Omnipresent' Augustine. Issue 4 (September 2014) - Toom, Tarmo
Abstract This review article explores a new indispensable reference work on the reception of Augustine. It offers an overview of its content, structure, and methodology, as well as a critical assessment of its overall contribution to the study of Augustine. Goethe once remarked that, in the world, there are just a few voices, yet so many echoes. Augustine is definitely among the 'few voices', which have provoked all manner of friendly and unfriendly echoes. It is particularly important to realize that, apart from explicit citations and references in western literature, Augustine has also profoundly shaped medieval and modern culture through the subtle dissemination of his ideas into various spheres of life. This reference work not only provides a description of the current state of the reception of Augustine, but also adds the new results of the diligent work of the contributing researchers and identifies several topics that still need to be investigated.